Oklahoma - Auschwitz ("America", Kafka's first novel) - Kostić, Dragomir J. (Collection of Papers of the Faculty of Philosophy in Priština, 2014)
Novel America consists of a series of fragments. It is built on the principles of expansion and compression, in the writer describes the moment in detail what happened to Carl Rosmman, the main character of the novel (for instance, the conversation in the room captein of the ship, departure and appenings in the mansion near New York, meeting with Delamars and Robinsons, investiggation aganist Carl's Robinson and leaving the elevator in the hotel, departure and arrival at Delamars, Robinson and Brunelde), or it runs through certain events, and connects them collectively (the time at his uncle's, working at Occidental), when the lowet describes a space much longer elapsed time (in both cases, approximately two months(. Rosmann's character is all built on contrasts and oddities. He has all the losing and finding. Rossmannn is a lost umbrella, uncle finds; when losing an uncle (his uncle's favor), is in umbrella and so on and so on, and so on...
Keywords: precognition; alienation; misunderstanding; adventurism; Franz Kafka